Reducing extreme weather impacts in greenhouses: the effect of a new passive climate control system on nutritional quality of pepper fruits. (4th November 2021) - Piñero, María Carmen; Lorenzo, Pilar; Sánchez‐Guerrero, María‐Cruz; Medrano, Evangelina; López‐Marín, Josefa; del Amor, Francisco M
Abstract: BACKGROUND: Environmental conditions affect the quality of the fruits and their organoleptic properties. In low‐tech greenhouses, these environmental conditions are frequently not optimal for crops. Therefore, the present study demonstrates the effects of the use of an integrated passive heating and cooling system in a greenhouse located in the Mediterranean area on the quality of pepper fruits. RESULTS: The results indicate that the passive system utilized (i) improved many parameters, such as average weight of fruits, °Brix, glucose and fructose content, and P and K content; (ii) increased the values of b * and h ab *; and (iii) reduced total phenolic compounds, total amino acids content, and Fe and Zn content. However, the degree of the effect of the climatic factors on these parameters was also affected by harvest time. CONCLUSION: This novel study highlights the possibility of improving the nutritional quality of pepper fruits by modifying the environmental conditions through the use of passive heating and cooling systems at the same time as reducing the carbon footprint. © 2021 Society of Chemical Industry.